The Lived Experiences of Working Architecture Students in Coping Academic Stress as Regards to Plates Making - Juarez, Jane Claide; Martinez, Sammy James; Pajantoy, Crystal Jade; Pamintuan, Nissa Mae; Perido, Jovilyn; Requina, David Oswald; Serrano, Antoinette Jan; Tampe, Christine Mae C; Tenedero, Cynic; Mendigorin, Leon (IJECA (International Journal of Education and Curriculum Application), 2024)
This is a qualitative descriptive research that identify the challenges experienced by working architecture students. A content analysis was used to examine the nine working architecture students at the Technological University of the Philippines – Manila. Snowball sampling was used to identify the participants. The researchers conducted semi-structured interviews to gather data on the challenges faced by the students which includes identifying the main challenges, sub-challenges, effects, and coping mechanisms. The participants' narratives reveal the interrelation of factors affecting their ability to meet academic requirements and maintain a healthy lifestyle. It was found out that their academic performance is affected as they work with their respective part time job. While coping mechanisms such as seeking support, engaging in therapeutic activities, and maintaining integrity through consistent efforts are employed, the pervasive impact of these challenges on academic performance and well-being emphasizes the necessity for targeted interventions and support structures to foster a more conducive environment for the success and betterment of working architecture students. The study is instrumental in forming adaptive and inclusive educational policies, acknowledging the increasing prevalence of students managing multiple commitments which highlights the broader issue of work-life balance, this further recommends to institutions to adopt holistic approach that prioritize not only academic achievement but also the overall well-being of students.